Characterisation and expression of two late embryogenesis abundant (lea) protein families in soybean (Glycine max) - Bang, Cao Phi (Academia Journal of Biology, 2015)
Late Embryogenesis Abundant proteins (LEA) are abundantly present in late embryogenesis and play an important role in the development of embryos. Many LEA subfamilies were reported to have a major role in abiotic stress tolerance in plants. According to current classification, LEA5 family and SMP family belong to the LEA superfamily. In this study, we identified five coding genes for each of these families in the genome of the soybean (Glycine max). In the case of soybean LEA5 genes, there is generally only one intron per gene, except for GmLEA5-3. This gene was not annotated in the soybean genome and had no intron. All of the soybean LEA5 predicted proteins were small in size, weakly acidic but highly hydrophilic. The SMP genes have one or more introns interspersed within the coding region. Their predicted proteins were weakly acidic and phydrophilic. All of the soybean LEA5 and SMP genes did not express in vegetative tissues while most of them were tissue-specifically expressed in seeds. The expression level increased in accordance with seed development, and arrived at the maximum level 42 days after flowering. The tissue-specific expression suggested that these genes played an important role in the development of soybean seeds. Briefly, for the first time, the characters and the expression of the soybean LEA5 and SMP genes were reported, paving the way for future gene function research about these two LEA families in Leguminosae plants.